2020
DOI: 10.1371/journal.pone.0240833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VEGF-A secretion from tumor cells under cellular stresses in conventional monolayer culture and microfluidic three-dimensional spheroid models

Abstract: Vascular endothelial growth factor (VEGF) is a major cytokine in tumor biology affecting tumor survival, aggressiveness and pro-angiogenetic activities. In addition, cellular stresses often result in aggressive pro-angiogenetic behavior in tumors. For in vitro study, conventional monolayer cell culture has been broadly exploited; however, it often provides limited information due to its different microenvironment from that in vivo. Recently, three-dimensional (3D) cell spheroid culture provides in vivo-like mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 82 publications
3
8
0
Order By: Relevance
“…Massive production of spheroids was used to challenge spheroids to two different cellular stresses: nutrient deprivation (serum concentration) and hypoxia (HIF inhibition). 3D cultures obtained data confirmed in vivo observation where stress conditions favoured the increase of VEGF secretion and induction of malignancy processes [99] . This study confirmed the impact of ECM variation in tumour malignancy as well as demonstrated that microfluidic approaches represent an interesting tool for massive 3D cultures and analysis.…”
Section: D Culture Methods Of Primary Bone Tumourssupporting
confidence: 81%
See 1 more Smart Citation
“…Massive production of spheroids was used to challenge spheroids to two different cellular stresses: nutrient deprivation (serum concentration) and hypoxia (HIF inhibition). 3D cultures obtained data confirmed in vivo observation where stress conditions favoured the increase of VEGF secretion and induction of malignancy processes [99] . This study confirmed the impact of ECM variation in tumour malignancy as well as demonstrated that microfluidic approaches represent an interesting tool for massive 3D cultures and analysis.…”
Section: D Culture Methods Of Primary Bone Tumourssupporting
confidence: 81%
“…3 ). A microfluidic chip was developed for the production of OS spheroids in mass (up to 5000) [99] . Microfluidic device was treated with a surfactant (Synperonic®) to generate a non-adherent surface that favoured the generation of MG63 spheroids in a similar way as non-adherent plates.…”
Section: D Culture Methods Of Primary Bone Tumoursmentioning
confidence: 99%
“…Then the same tissues were subjected to western blotting, and we found that LBH upregulation significantly decreased the protein expression of Vimentin, p-CRYAB and CRYAB, and increased E-cadherin expression (Figure 1C), showing inhibited EMT progression, which is consistent with our previous results in NPC cells. LBH upregulation also significantly decreased VEGFA expression, which was verified by whole-slide images of anti-VEGFA staining (Figure 1A, C), whose upregulation and secretion were generally considered angiogenic [32,33]. Moreover, H&E staining indicated that for both CNE2 and SUNE1 NPC xenografts, the tissues of LBH-overexpressing tumors were well-differentiated compared to the controls, exhibiting relatively epithelial characteristics, while the tissues of Lv5NC tumors showed poorly-differentiated, relatively mesenchymal characteristics (Figure S5).…”
Section: Lbh Upregulation Is Associated With Attenuated Angiogenesis Emt Progression and Vegfa Expression In Npc Tumor Xenograftssupporting
confidence: 53%
“…These studies mostly focused on the influence of molecular gradients in cell morphology, or the adhesive properties of OS cells under shear flow or at various temperatures/pHs. In one study, the secretion of VEGF type A from MG63 cells was investigated [100]. OS cells were cultured either in a monolayer or in a spheroid model fabricated in microfluidic chips.…”
Section: Microfluidic Platformsmentioning
confidence: 99%
“…The results demonstrated lower cell viability under higher stress levels (due to inhibition of HIF and decreased nutrient supply) in both cell culture models. However, in monoculture, the secretion of VEGF decreased in stressful conditions, which does not correspond to the in vivo situation [100]. In another study, a microfluidic platform was developed to test the efficacy of methotrexate and methotrexate-loaded nanoparticles [146].…”
Section: Microfluidic Platformsmentioning
confidence: 99%